Comparing the Effect of Different Extraction Methods and the Role of Solvent Polarity on Total Phenolic and Flavonoid Contents and Antioxidant Activities of Ferula persica - Elham Majidaee; Seyyedeh Raheleh Hosseyni Talei; Sepideh Gholamnezhad; Mohammad Ali Ebrahimzadeh (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Ferula persica is traditionally used in treatment of diabetes and rheumatism. There is no report on antioxidant activity of this plant. This investigation was designed to study the impact of extraction methods and solvent polarity on phenolic contents and antioxidant activities of F. persica root and aerial parts. Materials and methods: In this experimental research, the plant was extracted by three methods. Also, it was extracted successively with solvents of different polarities. Antioxidative capacities of the extracts were assessed by three methods. Total phenolic and flavonoid contents were also determined. Results: The highest yield of extraction was achieved by soxhlet assisted extraction. In DPPH radical scavenging activity, the soxhlet extract of aerial parts showed a higher activity which was significantly different from other extracts (IC50= 279.3 ± 9.0 µg ml-1, P<0.0001). Methanol extract of aerial parts exhibited the highest antioxidant capacity (P<0.0012). In reducing power assay, compared to other extracts, root ultrasonic and soxhlet assisted extractions showed the highest antioxidative activities (P<0.0044). Methanolic aerial parts showed the highest activity. The extracts did not show high activities in nitric oxide radical scavenging activity. IC50 for aerial parts ultrasonic extract was 159.7 µg/ml and the IC50 for ethyl acetate extract of aerial parts was 441.2 µg/ml which showed significantly higher activity compared to other extracts (P<0.0001). Conclusion: In this study, the extraction methods significantly influenced antioxidant capacities and total phenolic content. Ethyl acetate and n-butanol were found to be more suitable for extraction of phenolics. Maceration is believed to be a more efficient method for extraction of phenolics.